Comparison of physicochemical composition, antioxidant activity and common phytochemicals of selected BARI mango varieties and commercial cultivar, Langra - Ashfak Ahmed Sabuz; Mohammad Mainuddin Molla; Md. Hafizul Haque Khan; Md. Golam Ferdous Chowdhury; Shahnaj Pervin; Mahfujul Alam; Anjumanara Khatun; Ifran Al-Rafi; Md. Ridowan Al-Zihad (Food Chemistry Advances, 2024)
Background: Bioactive compounds and antioxidant activity in mango play significant role in human health. Present study was conducted to investigate the physicochemical and nutritional compositions, bioactive phytochemicals and antioxidant activity of the selected BARI mango varieties and commercial cultivar Langra. Scope and approach: Antioxidant activity, total phenolic content, ascorbic acid, total carotenoids and ß-carotene content of the mangoes were determined. TPC were assessed using high-performance liquid chromatography. Key findings & conclusions: Moisture, ash, total soluble solids, pH, total acidity and total sugar of the BARI mango varieties ranged from 77.50 to 83.60 %, 0.10–0.17 %, 17.50–23.00 °B, 3.45–4.37, 0.64–0.76 % and 9.46–13.46 % whereas, those were 76.33 %, 0.20 %, 17.63 °B, 4.25, 0.63 % and 9.79% respectively for Langra. Phytochemicals; TPC, AA, total flavonoids, TC, ß-carotene and total anthocyanin content of BARI mango ranged from 100.10 to 207.40 mg GAE/g, 9.34–9.52 mg/100 g, 0.38–1.04 mg QE/g, 2.76–3.87 mg/100 g, 178.02–298.00 µg/100 g and 147.26–186.42 mg/100 g whereas, the Langra contained 210.90 mg GAE/g, 9.53 mg/100 g, 1.38 mg QE/g, 4.21 mg/100 g, 314.00 µg/100 g and 189.22 mg/100 g respectively. Total antioxidant capacity, ferric reducing antioxidant power, reducing power capacity, metal chelating capacity, nitric oxide free radical scavenging activity and half-maximal inhibitory concentration (IC50) ranged from 108.10 to 504.00 µg of ascorbic acid/mg of extract, 121.70–244.60 mg/100 g, 6.24–18.70 µg/mL, 33.89–162.60 %, 33.89–70.20 µg/mL and 25.90–27.90 µg/mL whereas, Langra contained 194.25 µg of ascorbic acid/mg, 229.20 mg/100 g, 2.54 µg/mL, 177.80 %, 53.74 µg/mL and 25.11 µg/mL respectively.